HUMOR, POLITENESS, AND INTIMACY IN FAMILY COMMUNICATION: TRACING EFL LEARNERS’ SOCIOLINGUISTIC DEVELOPMENT THROUGH DAILY WHATSAPP EXCHANGES - Andi Nurhikmah; Anugerah Febrian Syam; Areski Wahid (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2025)
Despite growing interest in digital communication and pragmatic development, limited research has examined how everyday family WhatsApp interactions contribute to EFL learners’ sociolinguistic growth. Addressing this gap, the present study investigates how humor, politeness, and intimacy shape learners’ communicative development in home-based digital environments. Employing a qualitative, micro-longitudinal ethnographic design, the study involved three EFL learners who regularly interacted with siblings and parents through WhatsApp. Data were drawn from screenshots and exported chat logs, supported by field notes and reflexive journals documenting contextual details. Data analysis combined Thematic Analysis, Computer-Mediated Discourse Analysis, and sociopragmatic frameworks to trace patterns across six months. Results reveal clear developmental trajectories: blunt humor and unmitigated requests gradually declined, while affiliative humor, indirect requests, supportive moves, and structured confirmation strategies increased. Intimacy emerged as a key factor mediating pragmatic flexibility, and digital affordances such as emojis and laughter tokens played an important role in meaning-making. These findings highlight the value of everyday digital communication as a rich environment for sociolinguistic development and suggest practical implications for EFL pedagogy, emphasizing the integration of naturalistic CMC-based activities in pragmatic instruction.